Effect of stromal cell derived factor-1 alpha release from heparin-coated Co-Cr stent substrate on the recruitment of endothelial progenitor cells - Kang, Sung Nam; Park, Chungwon; Kim, Seong Min; Park, Ki Wan; Park, Bang Ju; Han, Dong Keun; Joung, Yoon Ki (SPRINGER, 2015)
The restoration of a damaged endothelium might be a fascinating way to reduce significantly late-thrombosis and restenosis in the stent treatment. It has been recently reported that the recruitment of endothelial progenitor cells (EPCs), capable for repairing a damaged endothelium, can be important in the vascular stent application. Therefore, we focused on the hypothesis that stromal cell-derived factor-1 alpha (SDF-1 alpha) acts as a key chemokine for the mobilization and recruitment of EPCs to the damaged endothelium lesion. In this study, the effect of SDF-1 alpha released from a cobalt-chromium alloy (Co-Cr) plate, vascular stent material, was investigated on the recruitment of EPCs in vitro. Dopamine-conjugated heparin was synthesized to introduce heparin onto Co-Cr. Heparin-coated Co-Cr surfaces were examined by water contact angle and attenuated total reflectance-Fourier transform infrared (ATRFTIR) to prove successful coating of heparin. Finally, SDF-1 alpha was bound to the coated heparin derivative. Amounts of loaded and released SDF-1 alpha were measured by ELISA, and the recruited EPC by released SDF-1 alpha was evaluated using two different migration assays. The quantity of SDF-1 alpha bound to the heparin-modified surface increased in a concentration-dependent manner and SDF-1 alpha was released over 28 days. Transwell migration assay revealed that soluble SDF-1 alpha released from the heparin-coated Co-Cr induced significantly more EPC recruitment than bare Co-Cr and heparin-coated Co-Cr. More importantly, fibrin gel migration assay further demonstrated that EPCs evidently respond to heparin-based substrate with SDF-1 alpha and this type of behaviors was surprisingly found at as low level as less 1 ng/day of SDF-1 alpha. These results are strongly encouraging for further in vitro and in vivo studies.
Keywords: DRUG-ELUTING STENTS; RE-ENDOTHELIALIZATION; VASCULAR GRAFTS; IN-VITRO; HYDROGELS; SURFACE; BIOCOMPATIBILITY; ENHANCEMENT; SDF-1-ALPHA; CONJUGATE